Factors affecting student performance in accounting subject: A case of pre-diploma students / Nur Syazwani Mohammad Fadzillah …[et al.] - Mohammad Fadzillah, Nur Syazwani; Jamaluddin, Junaidah; Ahmad, Mohd Azmi Nias; Mohd Din, Norlaila; Abdul Jabar, Faizan (Universiti Teknologi MARA Cawangan Pahang, 2020)
Learning accounting subjects requires students to understand the basic principles of accounting and to practice appropriate learning approaches so that students can have better understanding. However, effective understanding in accounting subjects is influenced by several factors that will also influence student achievement in the accounting subjects. Therefore, this study aims to identify factors that influence students' performance in accounting subjects at the pre-diploma level. A key factor that has been considered is the early exposure in accounting at secondary school. While, other factors included were gender, interest and parental influence. The sample used in this study was students from Pre-Diploma Commerce program at Universiti Teknologi Mara, Cawangan Pahang, Kampus Jengka. Questionnaires were distributed to students to obtain data. Students' performance was measured based on their total marks in the subject of Introduction to Accounting (ACC030). Data were analyzed using the SPSS package to test hypotheses to determine the relationship between factors and student performance. The findings showed that early exposure and students’ interest influence the performance of pre-diploma students in accounting subject. Hopefully, the findings of this study will help the teaching and learning of accounting subjects to be more effective.